Effect of rubber powder particle on the strength of foamed concrete - Abdullah, Siti Radziah; Riwayat, Akhtar Izzaty; Hossain, M. Zakaria (Geotec., Const. Mat. &Env., 2017)
Foamed concrete has become one of the most commercialized materials used in construction industry. It has different characteristics compared to conventional concrete such as self-compacting without vibration, flowability and low density. Even though foamed concrete has many advantages but it possess low strength limiting its use in many applications. This research aims to investigate the potential of foamed concrete incorporating rubber powder as additive to improve its strength. The amount of rubber powder added as filler in foamed concrete are 0%, 3%, 6%, 9% and 12%. A total of 15 concrete cubes and 15 concrete cylinders were cast with difference percentages of rubber powder in order to evaluate its compressive and splitting tensile strength. The mix design was set to achieve a density of 1800 kg/m3. The experiments on fresh state properties show that the foamed concrete has a very low workability as the percentage of rubber increase. However, the compressive and splitting tensile strengths for foamed concrete containing rubber are higher compared to control foamed concrete. The addition of 9% of rubber brought a significant increase for compressive strength and tensile strength of 122% and 43%, respectively, as compared to foamed concrete without rubber powder. Based on the results, it was concluded that the optimum percentage of rubber in this research was 9% for the highest compressive and tensile strength for foamed concrete.